Membangun Hubungan Berkelanjutan Sektor UMKM dan Perbankan - S, Basir; Prajawati, Maretha Ika (Fakultas Ekonomi, UIN Maliki Malang, 2020)
SMEs hope that their relationship with banks will provide them with ease in accessing capital and financing accordingly, with reasonable costs and conditions, where they expect a mutually beneficial and sustainable relationship in the future. The loyalty of SMEs in using banking services, the length of their relationship and reciprocal relationship shows that SMEs benefit from this relationship. One key element in their relationship is mutual trust. The results of the research show that trust affects effective commitment (affective commitment). Social bonding to affective commitment has a positive and significant effect on affective commitment. Affective commitment has a positive impact on behavioral intention. Attractive alternatives in their role of affective commitment and behavioral intention show that the variable attractive of alternative can strengthen the relationship of affective commitment and behavioral intention.